The principle of ne bis in idem in international criminal law : balancing the interests of individuals, states, and the international community - Nuridzhanian, Gaiane (Abingdon, Oxon: Routledge, Taylor & Francis Group, 2024)
"The legal principle of ne bis in idem proclaims that no person shall be tried twice for the same matter. This principle is important in theory and practice, as it safeguards a fundamental individual interest and spares the accused the burden of a repeat trial. This book provides a comprehensive examination of the ne bis in idem principle in international criminal law. Readers will find a detailed account of ne bis in idem rules in the law and practice of the International Criminal Court and other international criminal courts. The book also examines international law ne bis in idem rules that govern the domestic prosecution of international crimes. The book will be a valuable resource for researchers, academics and policy-makers working in the areas of International Criminal Law and International Human Rights law. It will be of particular use to those interested in defense rights, admissibility of cases before international criminal courts, and issues arising from prosecution of international crimes in multiple criminal jurisdictions"--
Definition, rationale, and basic concepts -- Ne bis in idem in international law -- Ne bis in idem in international human rights law -- Ne bis in idem in Article 20(1) of the Rome Statute -- Ne bis in idem in Article 20 (2) of the Rome Statute -- Ne bis in idem in Article 20 (3) of the Rome Statute -- Concluding reflections.
Includes bibliographical references and index.
Keywords: Rome Statute of the International Criminal Court -- (1998 July 17); Double jeopardy; International Criminal Court; International law and human rights; International criminal law